God in the courtroom : the transformation of courtroom oath and perjury between Islamic and Franco-Egyptian law - Bechor, Guy. (Studies in Islamic Law and Society, 2012)
This volume compares the courtroom oaths of both Islamic and modern Egyptian legal systems, blending elements of legal history, comparative law, theology, philosophy and culture. Until now, academic research has paid little attention to the subject of the courtroom oath in the Islamic or Egyptian legal systems. As such, it might appear as if modern legislation in the Arab world on this subject forms the natural continuation of Islamic law, or that there are no significant differences between these two legal approaches. This unique study seeks to rectify this impression by examining the institution of the courtroom oath on the basis of three criteria: Islamic law, which discusses the oath in the context of the judicial proceeding, including debate between different schools and interpreters; the sources and approach of Arab law on this subject; and, lastly, the core of this book - a detailed legal comparison between the Islamic oath and the Arab oath. In itself, this is a study in legal history examining the origins, character, sources,and doctrines of the oath in Arab law and at the same time, it is a comparative study of Islamic and contemporary Arab law in this field.